EMERGING TRENDS IN GENERAL MEDICAL PRACTICE IN HARNESSING DIGITAL HEALTH TECHNOLOGIES FOR IMPROVED PATIENT CARE - Khaled Saleh Salem Lasloom, Salem Saleh salemAlsallum, Rashid Hader Hassan Al-Yami, AwadJaber Nasser Alyami, Rahma Mahdi Mubark Al Ajmi, Jaber Saleh MohmmadLesloum, (Chelonian Research Foundation, 2023)
Digital health technology is revolutionizing the understanding of care in general healthcare. This article investigates patterns utilizing these advances to move forward in persistent care. Through a comprehensive writing survey, we look at the current state of Digital health innovations, their integration into healthcare, and their effect on understanding care. The strategies utilized within the inquiry, the advancement of these strategies, and the theme are examined. ComScore highlighted vital data concerning the benefits and challenges of actualizing. Healthcare innovation in authority. Finally, the article talks about the potential of these advancements to progress persistent care and offers proposals for future investigations and usage strategies. Keywords: Digital health, General medical practice, Patient care, Emerging trends, Technology integration